A personalised diet study: The interaction between ApoA2 −265T > C polymorphism and dietary inflammatory index on oxidative and inflammatory markers and lipid profile in patients with type 2 diabetes mellitus: A cross‐sectional study. Issue 7 (1st May 2021) - Karimi, Elmira; Tondkar, Pourya; Sotoudeh, Gity; Qorbani, Mostafa; Rafiee, Masoumeh; Koohdani, Fariba
Abstract: Background: This study aimed to investigate the interaction between dietary inflammatory index (DII) and apolipoproteinA2 265T > C (ApoA2 −265T > C) polymorphism on inflammatory and oxidative markers and lipid profile in type 2 diabetes mellitus (T2DM) patients. Methods: In this cross‐sectional study, 157 patients with T2DM were recruited. A food‐frequency questionnaire was used for DII calculation. Inflammatory, oxidative and lipid biomarkers were measured. Real‐time polymerase chain reaction (PCR) method was used for ApoA2 genotyping determination. Results: In the current study, serum 8‐iso‐PGF2α and CRP were significantly higher, and serum SOD activity was significantly lower in subjects with CC genotype than TT homozygous in both crude and adjusted (for DII and AAs intake) models. Also, C‐allele carriers compared with people with TT genotype had lower PTX3 in both models. In addition, serum TG level was significantly higher in TC genotype than TT homozygous in adjusted model. Moreover, subjects with CC homozygous and high DII level had significantly higher 8‐iso‐PGF2α level compared to those with TT genotype and low DII (reference group) in adjusted (for BMI, age, sexuality and AAs intake) model. Our results also showed that in TC genotypes with low DII and CC homozygous with both low and high DII, PTX3 concentrations were significantly lower than the reference group. In addition, CC carriers with low DII had significantly higher CRP level compared to the reference group. Moreover, our results reported significant higher TG in TC genotype with low DII and also higher total cholesterol level in CC genotype with low DII than the reference group. Conclusion: These findings indicate that CC genotype might predict higher inflammatory and oxidative status level compared to T allele carriers. An inflammatory diet may accelerate oxidative stress in subjects with CC genotype. However, the association between APOA2 −265T > C polymorphism and inflammation and lipid profile is presented less modifiable by DII.